Training and Its Role in Enhancing Job Performance: An Applied Study on the Employees of Al-Qardah Al-Shati Municipal Council - Ahmad Tarjem Mohamed Ali (Journal of Scientific and Human Dimensions, 2026)
The study aimed to examine the impact of training on enhancing the job performance of employees at Al-Qardah Al-Shati Municipal Council. It adopted a descriptive-analytical approach and used a questionnaire as the main tool to collect data from a random sample of 277 employees out of a total population of approximately 900. The study focused on three key dimensions of the training process: training needs assessment, training program design, and training implementation and evaluation, with job performance as the dependent variable. The results revealed that training has a significant positive effect on developing employees’ skills and knowledge, enhancing their professional competence, and improving the quality of services provided to citizens. The findings also indicated that systematically assessing training needs, designing structured programs, and implementing them according to well-planned strategies substantially contribute to improving job performance. The study highlights the importance of continuous investment in training as a strategic tool for developing human capital, enhancing organizational efficiency, and achieving citizen satisfaction.